X-ray photoelectron spectroscopy under real ambient pressure conditions. (27th June 2017) - Takagi, Yasumasa; Nakamura, Takahiro; Yu, Liwei; Chaveanghong, Suwilai; Sekizawa, Oki; Sakata, Tomohiro; Uruga, Tomoya; Tada, Mizuki; Iwasawa, Yasuhiro; Yokoyama, Toshihiko
Abstract: We have developed an ambient pressure hard-X-ray photoelectron spectroscopic system equipped with a differential pumping system at BL36XU of SPring-8. Photoelectron spectra from a Au(111) surface were recorded using excitation light of 8 keV focused to 20 × 20 µm 2 and adopting an aperture diameter of 30 µm at the entrance of the electron lens and a working distance of 60 µm. The Au 4f and 3d5/2 spectra were measured by increasing the ambient pressure from 1 Pa to atmospheric pressure and demonstrated that the instrument is capable of measuring the photoelectron spectrum under atmospheric pressure.